Characterization of Two Zygnema Strains (Zygnema circumcarinatum SAG 698-1a and SAG 698-1b) and a Rapid Method to Estimate Nuclear Genome Size of Zygnematophycean Green Algae - Feng, Xuehuan; Holzinger, Andreas; Permann, Charlotte; Anderson, Dirk; Yin, Yanbin (Frontiers in Plant Science, 2021)
Zygnematophycean green algae (ZGA) have been shown to be the closest relatives of land plants. Three nuclear genomes of the class Zygnematophyceae have been recently published, and more genomes are under way. Here we analyzed the commonly used Zygnema circumcarinatum strains SAG 698-1a (mating +) and SAG 698-1b (mating -) and found distinct cell sizes and other morphological differences. The molecular identities of the two strains were further investigated by sequencing their 18S rRNA, psaA and rbcL genes. These marker genes of SAG 698-1a were surprisingly much more similar to Z. cylindricum (SAG 698-2) than to SAG 698-1b. Phylogenies of these marker genes also showed that SAG 698-1a and SAG 698-1b were well separated into two different Zygnema clades, where SAG 698-1a was clustered with Z. cylindricum, while SAG 698-1b was clustered with Z. tunetanum. Additionally, physiological parameters like ETRmax values differed between SAG 698-1a and SAG 698-1b, after 2 months of cultivation. Moreover, de-epoxidation states of the xanthophyll cycle pigments were also different. All these indicate physiological differences between the strains. Furthermore, the two strains could not conjugate, and significantly differed in the thickness of the mucilage layer. Additionally, ZGA cell walls are highly enriched with sticky and acidic polysaccharides, and therefore the widely used plant protoplast extraction protocols do not work well in ZGA protoplast generation. Here, we also reported a fast and simple method, by mechanical chopping, for efficient nuclear extraction in the two SAG strains. More importantly, the extracted nuclei were further used for nuclear genome size estimation of the two Zygnema strains by flow cytometry (FC). To confirm the FC result, we have also used other experimental methods for nuclear genome size estimation of the two strains. Interestingly, the two strains were found to have very distinct nuclear genome sizes (313.2 ± 2.0Mb in SAG 698-1a vs. 63.5 ± 0.5Mb in SAG 698-1b). Our multiple lines of evidence strongly indicate that the strain SAG 698-1a possibly had been confused with SAG 698-2 prior to 2005, and most likely represents Z. cylindricum or a closely related species.